2018
DOI: 10.1021/acsami.8b08496
|View full text |Cite
|
Sign up to set email alerts
|

Loading across the Periodic Table: Introducing 14 Different Metal Ions To Enhance Metal–Organic Framework Performance

Abstract: Loading metal guests within metal-organic frameworks (MOFs) via secondary functional groups is a promising route for introducing or enhancing MOF performance in various applications. In this work, 14 metal ions (Li, Na, K, Mg, Ca, Ba, Zn, Co, Mn, Ag, Cd, La, In, and Pb) have been successfully introduced within the MIL-121 MOF using a cost-efficient route involving free carboxylic groups on the linker. The local and long-range structure of the metal-loaded MOFs is characterized using multinuclear solid-state NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
116
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(119 citation statements)
references
References 74 publications
3
116
0
Order By: Relevance
“…8 ppm arises from phenyl hydrogen, and the H3 resonance at ca. 3 ppm corresponds to the bridging hydroxyl group that connects adjacent Al atoms. , With basic spectral assignments given, we now discuss how the 13 C and 1 H NMR spectra in Figure and Figure S5 evolve with increasing thermal treatment temperatures and times, relating spectral changes to structural features.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 ppm arises from phenyl hydrogen, and the H3 resonance at ca. 3 ppm corresponds to the bridging hydroxyl group that connects adjacent Al atoms. , With basic spectral assignments given, we now discuss how the 13 C and 1 H NMR spectra in Figure and Figure S5 evolve with increasing thermal treatment temperatures and times, relating spectral changes to structural features.…”
Section: Resultsmentioning
confidence: 99%
“…The overlapping C1 and C2 resonances at ca. 172 ppm originate from free (C2) and Al-coordinated (C1) carboxyl carbon sites, , while the 13 C resonances at ca. 135 and 130 ppm are assigned to the unsubstituted C3 phenyl carbon site and the carboxyl-substituted C4/C5 phenyl carbon sites, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The resonances at ca. 134.9 and 130.0 ppm originate from the C3, C4, and C5 sites of phenyl carbons (Figure b). , The less intense signals at ca. 50 ppm belong to residual guest methanol molecules which were subsequently removed during thermal treatment.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned earlier, the signal at 172 ppm in the 13 C spectrum of MIL-121 originates from two overlapping resonances: C1 from the Al-coordinated carbon atom and C2 from the free carboxylate groups. Our previous study showed that, once the free carboxylate groups are doped with extra-framework metal ions, new signals often appear on the lower-field side of the peak at 172 ppm, which is due to the C2 site of the free COO – group interacting with the newly introduced metal ions. In the 13 C spectrum of Pt-HMIL-121, an extra peak indeed appears at ca.…”
Section: Resultsmentioning
confidence: 99%
“…In the particular case of MIL-121 and loading with Ca 2+ , detailed characterization was performed by 43 Ca NMR. [20] (iii) The study by natural abundance 43 Ca NMR of bioceramic materials based on silico-carnotite, Ca 5 (PO 4 ) 2 SiO 4 , synthesized mechanochemically: calculated δ iso ( 43 Ca) were used to analyze carefully the experimentally determined results. [21] 43…”
mentioning
confidence: 99%